Novas configurações na publicidade: análise do uso de estratégias e táticas diferenciadoras na publicidade de bebidas alcoólicas destiladas - Custodio, Luciana Freitas (2009)
This paper studies the distilled spirits ad announcers that, having their ads restricted by the Regulation (BRA) No 9.294 and by CONAR, search for alternative ways of communication and persuation of their targets. It were examined the differentiative strategies and tactics of communication used by those ad announcers, once it is forbidden to advertise that kind of drink on radio and television networks between six AM and nine PM. Also the advertising shall not link alcohol consumption to sports or to driving nor create the impression that the consumption of alcohol contributes towards a better performance of any activity or social and sexual success. To avoid these restrictions the ads had the intention to produce sensation of innovation and unconventionality towards an effective idea for brand communication and product selling. The starting point was the notion of the conventional media banalization such as television, outdoor, magazine advertisement, etc. and as a consequence the indifference of the receivers to those advertising messages that use traditional media. The research adopted concepts such as guerrilla marketing, coined by J. Conrad Levinson and the studies of Bauman about the consumption in Liquid Life . The Peircean Semiotic method from the point of view of Lucia Santaella was adopted to analyze the advertising campaign in the last chapter. The corpus analysis is composed by campaigns that adopted differentiative communication strategies to communicate and promote the distilled spirits during the period 2000-2009